Development of an analytical method involving thiol methylation for the analysis of pentachlorothiophenol in food using gas chromatography-tandem mass spectrometry - Junhyeong Park; Adebayo J. Akinboye; Joon-Goo Lee (Food Chemistry: X)
Organic pollutants such as pentachlorothiophenol are a major environmental and food safety hazard owing to their degradation resistance and bioaccumulation potential. Since existing methods for detecting and quantifying PCTP are applicable only to environmental and aquatic samples, it is imperative to develop methods applicable to foods. Herein, a method involving gas chromatography-tandem mass spectrometry and optimized methylation conditions is proposed for quantifying PCTP concentrations in food. The method was validated using six food samples, and the performance parameters were found to be within acceptable standards. Reproducibility was the most significant factor influencing the measurement uncertainty. An analysis of 870 food samples covering agricultural, livestock, and fishery categories showed PCTP concentrations ranging from not detected (ND) to 13.63 ng/g wet weight, with dairy products (ND to 4.97 ng/g) showing the highest level. In animal-derived food, PCTP was detected only in eggs (ND to 3.10 ng/g) and mussels (ND to 4.36 ng/g).